Answer:
x > -15
Step-by-step explanation:
-x / 3 < 5
(-x / 3) * 3 < 5 * 3
-x < 15
x > -15 (Remember to flip the sign when multiplying or dividing an inequality by a negative number.)
5 (3m+2p) -4m= 15m +10p -4m
=11m +10p
--------------------------------------------------------
13p+11m-3p=10p -11m
-----------------------------------------------------------
Yes, 5 (3m+2p) -4m is equivalent to the expression 13p+11m-3p as i worked out for you.. Hope this helps you!!! =')
Answer:
6 7/24
Step-by-step explanation: